Regulation of bacterial DNA supercoiling: plasmid linking numbers vary with growth temperature. - Goldstein, E (1984)
The level of DNA supercoiling can be altered either by breaking-rejoining reactions that change the DNA linking number or by environmental changes that alter the helical pitch of DNA. In vitro, temperature changes alter helical pitch and, thus, supercoiling. We find that plasmids isolated from bacteria grown at different temperatures exhibit differences in DNA linking numbers. The differences in plasmid linking numbers offset the effect temperature is expected to have on supercoiling. These results are consistent with the hypothesis that fine control of DNA topology in bacterial cells is brought about by changes in linking number to maintain a constant value for supercoiling.